Effect of curing conditions on the compressive strength of crumb rubber concrete paving blocks - Ling, Tung Chai; Md. Nor, Hasanan (2007)
Crumb rubber represents a potentially valuable resource as a replacement of fine aggregate in concrete paving blocks (CPBs). The objective of this study was to investigate the effect of three curing conditions on compressive strength of crumb rubber CPBs. Four batches of crumb rubber CPBs where produced in a commercial plant with replacement of sand at 0%, 10%, 20% and 30% with crumb rubber by volume. Only 0% and 10% replacement of crumb rubber CPBs satisfied the 28 days compressive strength (30MPa) for 60mm thickness rectangular paving block to carry traffic load in accordance to Concrete Masonry Association of Australia (MA20). In general, the natural weather cured gives better compressive strength than air cured and water cured at 182 days of age. In addition, high volume of daily production of CPBs makes natural weather curing to be more applicable and economic.